The conceptual basis of the formation of linguistic identities of future interpreters (Pedagogy of Higher and Secondary Education, 2013)
Goroshkin I. A. The conceptual basis of the formation of linguistic identities of future interpreters.The article presents a generalized point of view on the training of future interpeters at the professional level of methodological concept (approach, principles of teaching), substantial (requirements for the content of training, socio-cultural training), technology (the basic forms, methods and meanings of training, the organization of independent work of students).
Keywords: training; language personality; interpreter methodological concept; informative; technological